The Influence of the Use of Animation on the Indonesian Language Learning Outcomes of Class XI Students of the Modern Rahmatul Asri Maroangin Modern Islamic Boarding School - Nur Fadilah A; Usman M; Syamsunir Syamsunir; Hasan Hasan (Universitas Muhammadiyah Enrekang, 2024)
This research aims to determine the influence of animated video learning media on Indonesian language learning outcomes for class XI Madrasah Aliyah Modern Rahmatul Asri Maroangin Islamic Boarding School. This research is quantitative research with an experimental study method with a One Group Pretest-Posttest Design. The population in this study was 15 students/santri. The results of data analysis obtained from the pre-test (Y) were lower than the post-test results (X), namely Y = 26 < 05, which means there is a real difference between Indonesian language learning outcomes in the pre-test and post-test data. The results of the analysis with the final test show that students/santri who were taught after using the animated video learning media had a positive impact compared to students who were taught before using the animated video learning media.